Learning Sociology in the Era of the Covid-19 Pandemic (Case Study at Eben Haezar Christian High School Manado) - Bawole, Welem Anthonie; Kerebungu, Ferdinand; Soputan, Grace Jenny (Technium Social Sciences Journal, 2023)
This study aims to 1) analyze, describe, and interpret the effectiveness of learning Sociology at Eben Haezar Christian High School Manado during the Covid-19 Pandemic, 2) analyze, describe, and interpret the application of Sociology learning strategies at Eben Haezar Christian High School Manado during the Covid-19 Pandemic. The type of research used in this research is descriptive qualitative research with a phenomenological approach. Data collection techniques used are observation, interviews, and document studies. The research location was Eben Haezar Manado Christian High School with a research focus, namely exploring Sociology learning strategies for social studies class students at Eben Haezar Manado Christian High School during the Covid-19 Pandemic. The results showed that the implementation of Sociology learning at Eben Haezar Manado Christian High School had been carried out well, this was done by teachers and administrators using effective and efficient learning. Learning strategies using online applications during the Covid-19 pandemic can streamline Sociology online learning at Eben Haezar Manado Christian High School, as shown from the learning outcomes of each assessment exceeding 80% of students getting KKM scores and the results of observations of students’ activeness in learning activities increased significantly namely in the first observation, it reached 34% with a value of 2.40 in the less category while in the second observation, it increased to 62% with a value of 3.00 in the good category. The selection of online learning applications as a medium for delivering information and materials to students has implications for the effectiveness of online learning during the Covid-19 pandemic, so it needs to be of great concern to educators.